2018
DOI: 10.1289/ehp2644
|View full text |Cite|
|
Sign up to set email alerts
|

Decadal Changes in the Edible Supply of Seafood and Methylmercury Exposure in the United States

Abstract: Background:Methylmercury (MeHg) exposure is associated with adverse effects on neurodevelopment and cardiovascular health. Previous work indicates most MeHg is from marine fish sold in the commercial market, but does not fully resolve supply regions globally. This information is critical for linking changes in environmental MeHg levels to human exposure in the U.S. population.Objectives:We used available data to estimate the geographic origins of seafood consumed in the United States (major ocean basins, coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…The concentration and fate of mercury (Hg) in the ocean is controlled by the distribution of four principal species: mercuric ion (Hg[II]), elemental Hg (Hg 0 ), monomethyl-Hg (CH 3 Hg + ; MMHg), and dimethyl-Hg ([CH 3 ] 2 Hg; DMHg). MMHg is a neurotoxin that bioaccumulates in marine food webs and humans are primarily exposed through consumption of coastal and openocean fish, and marine mammals (Debes et al 2016;Madigan et al 2018;Schartup et al 2018;Sunderland et al 2018). Except for the Indian Ocean, which remains untested, MMHg and DMHg have been detected in the water column of every ocean basin (Mason and Fitzgerald 1993;Mason et al 1995;Sunderland et al 2009;Cossa et al 2011Cossa et al , 2018Wang et al 2012Wang et al , 2018Bowman et al 2015Bowman et al , 2016Heimbürger et al 2015;Munson et al 2015;Agather et al In press).…”
mentioning
confidence: 99%
“…The concentration and fate of mercury (Hg) in the ocean is controlled by the distribution of four principal species: mercuric ion (Hg[II]), elemental Hg (Hg 0 ), monomethyl-Hg (CH 3 Hg + ; MMHg), and dimethyl-Hg ([CH 3 ] 2 Hg; DMHg). MMHg is a neurotoxin that bioaccumulates in marine food webs and humans are primarily exposed through consumption of coastal and openocean fish, and marine mammals (Debes et al 2016;Madigan et al 2018;Schartup et al 2018;Sunderland et al 2018). Except for the Indian Ocean, which remains untested, MMHg and DMHg have been detected in the water column of every ocean basin (Mason and Fitzgerald 1993;Mason et al 1995;Sunderland et al 2009;Cossa et al 2011Cossa et al , 2018Wang et al 2012Wang et al , 2018Bowman et al 2015Bowman et al , 2016Heimbürger et al 2015;Munson et al 2015;Agather et al In press).…”
mentioning
confidence: 99%
“…Marine fish are the predominant vector of methylmercury exposure to human populations in many countries (Sunderland 2007) and thus such deposition patterns could potentially affect future human exposure to mercury. For example, marine fish supply more than 85% of the methylmercury intake to the United States population and the largest contributing source region is the Pacific Ocean (Sunderland et al 2018). Both the tropical Pacific Ocean and Indian Ocean are important supply regions for global tuna fisheries, which account for the dominant fraction of methylmercury exposure for many individuals (Sunderland et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, marine fish supply more than 85% of the methylmercury intake to the United States population and the largest contributing source region is the Pacific Ocean (Sunderland et al 2018). Both the tropical Pacific Ocean and Indian Ocean are important supply regions for global tuna fisheries, which account for the dominant fraction of methylmercury exposure for many individuals (Sunderland et al 2018). In figure 3, enhanced mercury deposition regions over the global oceans between 10°and 40°projected to result from satellite emissions correspond to some of the most important harvesting regions for global commercial fisheries (Zeller et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…An effect of geographical origin on concentrations of selected substances could also apply to fillet of fish from different catching areas, as geographical variations in substance concentrations have been observed. Sunderland et al (2018) studied geographical origins of seafood on the market in the United States and the concentration of methyl mercury, and showed that seafood was available from different catching areas and contributed to the methyl mercury exposure with different amounts. Several fish species caught in subareas of the Northeast Atlantic were investigated for methyl mercury and concentrations increased from north to south and by fish length (Azad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%